Two - Cole, Catherine (Disability Studies Quarterly, 2008)
"Two" is a short tale about a big story, a creative answer to the well-worn question, "What happened to you?" It is also a poetic meditation on duplicity, loss, and discovery — discovery that one has a body just as it begins to disappear.